Golimumab, a new human anti-tumor necrosis factor alpha antibody, administered intravenously in patients with active rheumatoid arthritis: Forty-eight-week efficacy and safety results of a phase III randomized, double-blind, placebo-controlled study. - Kremer, J; Ritchlin, C; Mendelsohn, A; Baker, D; Kim, L; Xu, Z; Han, J; Taylor, P (2010)
OBJECTIVE: To assess the efficacy and safety of intravenous administration of golimumab in patients with rheumatoid arthritis (RA). METHODS: Adult patients with RA in whom disease activity was persistent despite treatment with methotrexate (MTX) at a dosage of 15-25 mg/week for > or = 4 weeks were randomized to receive intravenous infusions of placebo plus MTX or intravenous infusions of golimumab at a dose of 2 mg/kg or 4 mg/kg, with or without MTX, every 12 weeks through week 48. Patients with <20% improvement in the swollen and tender joint counts could enter early escape and receive additional active treatment (week 16) or could have their dose regimen adjusted (week 24). The primary end point was the proportion of patients achieving a 50% response according to the American College of Rheumatology improvement criteria (ACR50) at week 14. RESULTS: The primary study end point was not met (at week 14, an ACR50 response was observed in 21% of the patients treated with golimumab plus MTX compared with 13% of the patients treated with placebo plus MTX [P = 0.051]). By week 24, significantly more patients treated with golimumab plus MTX had achieved an ACR50 response. Differences in the proportion of patients achieving an ACR50 response between the group receiving golimumab monotherapy and the group receiving placebo plus MTX were not significant at either week 14 (16% versus 13%) or week 24 (10% versus 9%). At week 48, the proportions of patients achieving ACR20 and ACR50 responses were highest among those who had received golimumab 4 mg/kg plus MTX (70% and 48%, respectively). Concomitant treatment with MTX was associated with a lower incidence of antibodies to golimumab. The most commonly reported adverse events through week 48 were infections (48% of patients treated with golimumab with or without MTX and 41% of patients receiving placebo plus MTX). CONCLUSION: The primary end point was not met. However, intravenously administered golimumab plus MTX appears to have benefit in the longer-term reduction of RA signs/symptoms in MTX-resistant patients, with no unexpected safety concerns.